Inkubační komora s nucenou cirkulací a notifikací stavu - Kadlubcová, Anna (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2021)
Tato bakalářská práce se věnuje senzorům, zejména teploměrům a vlhkoměrům, způsobu měření a regulace teploty v inkubační komoře. Hlavní část práce se věnuje návrhu, realizaci a testování zařízení. Inkubační komoru lze temperovat na teplotu, kterou lze nastavit v uživatelském rozhraní. Notifikace stavu se zobrazuje na webové stránce přes WiFi síť.

This bachelor thesis deals with sensors, especially thermometers and hygrometers, the method of measuring and regulating the temperature in the incubation chamber. The main part of the thesis is focused to the design, implementation and testing of the device. The incubation chamber can be tempered to a temperature that can be set in the user interface. Status notification is displayed on the website via WiFi network.
Incubation Chamber with Forced Circulation and Condition Notification
Keywords: Arduino; inkubační komora; inkubátor; nucená cirkulace; řízení teploty; senzor teploty; senzor vlhkosti; WiFi; WeMos D1 R1; ESP8266; Arduino; forced circulation; humidity sensor; incubation chamber; incubator; temperature control; temperature sensor; WiFi; WeMos D1 R1; ESP8266